A cultura do encontro na perspectiva dos encontros de Francisco de Assis - Sá, Daison Fermino de (2021)
The present dissertation, whose title is “The culture of the encounter in the perspective of the meetings of Francis of Assisi”, aims to perceive in the meetings of Francis of Assisi a life proposal for a culture of the encounter. The theme is discussed based on the problem of how to understand the process of the saint of Assisi to find himself and how, since his experiences of encounters, with so many other people and with Christ himself, he managed to provoke in other people and continues to provoke nowadays, an authentic search for the encounter with so many others, in particular those excluded and abandoned from society. The method of this work is synthetic analytical, that is, it will analyse some reports of the saint of Assisi, from Franciscan scholars who reflect on Franciscan theological anthropology, and at the same time, it will go through the narratives under the bias of the encounter to present a proposal of the meeting culture. The research is developed from the dimensions of “listening”, “discerning” and “proposing”. It is possible to notice that Francis of Assisi, was a man who in his time presented a new life proposal, responsible for transforming a social context, with a look turned to the Gospel that has repercussions on the lives of people, especially those who are sometimes placed the margins of society, “the lepers”. And today, not quite different, there are many who are discarded and who deserve attention and care, so that there is life and life in abundance, and the meeting is essential to feel the pain and joy of the other.